Quantifying the impact of nitric oxide calibration gas mixture oxidation on reported nitrogen dioxide concentrations. (March 2015) - Sweeney, Bryan P.; Quincey, Paul G.; Green, David; Fuller, Gary W.
Abstract: Chemiluminescent analysers for measuring nitric oxide (NO) and nitrogen dioxide (NO2 ) in ambient air are generally calibrated with certified gas standard cylinders of NO in nitrogen. Verification of the NOx and NO amount fractions has been carried out on many such 'on-site' calibration cylinders at air quality monitoring stations. These measurements indicate that significant numbers of these gas mixtures have become somewhat degraded, with several percent of the NO oxidised to NO2 . The effect of not compensating for this degradation on reported concentrations is discussed. If such degradation is not quantified and corrected for, there will be a systematic under-reporting of NO2 concentrations, which, due to the non-linearity of the effect, could reduce high reported NO2 concentrations at kerbside sites by around 20%. This could significantly reduce the number of reported exceedances of the NO2 limit value at such sites, compared to results obtained where there is no degradation of the NO cylinder. Highlights: Several percent of the NO in site calibration mixtures is often oxidised to NO2 . Analysis shows that the effect on reported NO2 can be a multiple of this percentage. Calculations with data from kerbside sites show significant underestimations of NO2 . The consequences for regulation and quality assurance procedures are discussed.